Características físicas dos Sistemas Convectivos de Mesoescala que afetaram o Rio Grande do Sul no período de 2004 a 2008 - Eichholz, Cristiano Wickboldt (2011)
The happening of Mesoscale Convective Systems (MCS) over a region causes impacts on the surface, that is usually associated with heavy precipitation, strong wind gusts and hail. This phenomenon is common in southern Brazil reach the Rio Grande do Sul (RS) and causes damage to its economy. Therefore the MCS study that reaching of RS is of great importance, as well as allowing a greater understanding of weather and climate of the region also provide knowledge to decision makers. Thus, the aim was to study the seasonal physics features of MCS whose genesis and maintenance happened southward of 20 º S, with life cycle of at least 6 h, with spontaneous initiation and normal dissipation and that reached the region covering the RS from 2004 to 2008, using the FORTRACC method (Forecasting and Tracking of Active Cloud Clusters). Channel 4 Geostationary Operational Environmental Satellite (GOES) images from 2004/01/01 to 2008/12/31, with 4 km x 4 km spatial resolution in your subsatellite point and ½ hour temporal resolution were used. These images were provided by DSA/CPTEC/INPE (Satellite Division and Environmental Systems/Center for Weather Forecast and Climate Studies/National Institute for Space Research) and served as a database for the use of the FORTRACC method. The results showed that: i) the MCS that affected the RS occurring majority in the warmest quarter of the year (JFM), ii) in the four quarters of the study period most of the MCS that affected the RS (64.7%) had lifetime between 6 and 12 h, iii) MCS with longer life cover larger areas, and iv) the minimum temperature (Tir) had lower mean values observed in the MCS in OND and JFM, v) in all periods of the year around 6.4% of the MCS showed a more linear format, approximately 64.0% have irregular shape and about 29.6% had more circular shape, vi) lower values of Tir are related to MCS with shape close to circular (eccentricity equal to or greater than 0.5) and longer duration, vii) the three phases of the life cycle of MCS that affected the RS can occur in a distributed manner throughout the day, viii) in all periods of years the births of MCS that affected RS occur predominantly in and around the grill that covers the RS, with a tendency to start over on the west side of the grid on the mainland; ix) in all quarters there is a tendency for the mean trend preferential be from west to east.